1979
DOI: 10.1111/j.1365-2621.1979.tb03449.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture, Fat, Protein And. Mineral Content of Mechanically Deboned Poultry Meat

Abstract: Mechanically deboned poultry meat samples from chicken broiler and turkey parts were analyzed for percentage moisture, fat, protein 'and mineral content. Moisture for turkey samples averaged 68.5%, fat 15.7% and protein 15.2%. Moisture, fat and protein for broiler samples averaged 72.2%, 14.4% and 13.4%, respectively. The minerals or elements detected in the largest amounts in ppm in decreasing order in turkey meat samples were K, Ca, Na, Cl, Mg, Fe, Cu, Zn, Rb and Al. In broiler meat samples the elements dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
3
6
1
2
Order By: Relevance
“…The results of the proximate composition of the MSCM obtained in this study were compared with data previously reported by other authors (Grunden et al 1972;Essary 1979;Froning 1981;Mott et al 1982;Hamm and Young 1983;Smyth and O'Neill 1997;Rivera et al 2000;Perlo et al 2006).…”
Section: Compositional Properties Of Mscm and Mscm Surimi-like Materialssupporting
confidence: 60%
“…The results of the proximate composition of the MSCM obtained in this study were compared with data previously reported by other authors (Grunden et al 1972;Essary 1979;Froning 1981;Mott et al 1982;Hamm and Young 1983;Smyth and O'Neill 1997;Rivera et al 2000;Perlo et al 2006).…”
Section: Compositional Properties Of Mscm and Mscm Surimi-like Materialssupporting
confidence: 60%
“…Nutrient composition data reported on MDP are mostly for moisture, fat and protein content (Froning, 1976;MacNeil e t al., 1978;Orr and Wogar, 1979;Essary, 1979). Limited data have appeared in the literature on amino acid composition (Essary and Ritchey, 1968;MacNeil et al, 1978), mineral content (MacNeil e t al., 1978;Murphy et al, 1979;Essary, 1979;Hamm and Searcy, 1981) and protein efficiency ratio (Brinkman and MacNeil, 1976;MacNeil et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of protein hydrolysates, such as fish, chickpea, shark muscle, and shrimp, were studied and can also be used in supplementation diets, high protein sports drinks, and therapeutic or enteric diets [8][9][10] . Considerable attention has been given to the use of MDCM as an ingredient in the manufacture of sausages and other meat products 11 , especially considering its nutritional quality 2, 12,13 . However, few studies have been published on the production and quality of MDCM protein hydrolysate.…”
Section: Introductionmentioning
confidence: 99%